2021
DOI: 10.1002/rth2.12525
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the coagulopathies associated with COVID‐19 and sepsis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 26 publications
1
52
3
Order By: Relevance
“…Although TF is recognized as one of the main actors in the inflammatory response during sepsis ( 43 ), an increase in circulating TF has never been described outside the DIC context ( 44 ). However, an increase in extracellular vesicle TF activity has been shown in COVID-19 ( 13 , 45 ) and moreover, other viral diseases including human dengue infection and HIV are characterized by an increased soluble TF release ( 46 , 47 ). Altogether, these results indicate that coagulation abnormalities of COVID-19-associated coagulopathy promote a procoagulant state.…”
Section: Discussionmentioning
confidence: 99%
“…Although TF is recognized as one of the main actors in the inflammatory response during sepsis ( 43 ), an increase in circulating TF has never been described outside the DIC context ( 44 ). However, an increase in extracellular vesicle TF activity has been shown in COVID-19 ( 13 , 45 ) and moreover, other viral diseases including human dengue infection and HIV are characterized by an increased soluble TF release ( 46 , 47 ). Altogether, these results indicate that coagulation abnormalities of COVID-19-associated coagulopathy promote a procoagulant state.…”
Section: Discussionmentioning
confidence: 99%
“…and another study found both TF and PAI-1 activity higher in COVID-19 patients than sepsis patients. 29 Thus, TF activity and inhibition of fibrinolytic activity could contribute to COVID-19-related thrombosis.…”
Section: Pulmonaryhistopathologyof Covid-19 and Non--covid-19 Ards Patients Including Characterization Of Cd61+ Platelet Thrombimentioning
confidence: 99%
“…Moreover, EV‐TF activity was significantly higher in COVID‐19 than in sepsis. 36 , 118 Guervilly et al. 36 found a higher EV‐TF activity in severe compared with nonsevere (moderate) COVID‐19 and a TF activity of more than 78.3 fM associated with thromboembolic events.…”
Section: The Contribution Of Pevs To Covid‐19mentioning
confidence: 99%
“… 117 Indeed, elevated levels of TF activity associated with EVs have been reported in COVID‐19, which may directly contribute to excessive coagulation. 36 , 70 , 118 In addition, ACE2, the primary receptor for SARS‐CoV‐2 infection in humans, is important in the regulation of the renin–angiotensin–aldosterone system and a deficiency of ACE2 is linked to enhanced risk of inflammation and thrombosis. 98 As COVID‐19 is increasingly viewed as a thromboinflammatory disease, 32 it is conceivable that platelet activation in COVID‐19 may be a consequence of the inflammation, organ damage, and pathological activation of the coagulation cascade, rather than a consequence of direct virus–platelet interaction.…”
Section: What Triggers the Release Of Pevs In Covid‐19?mentioning
confidence: 99%
See 1 more Smart Citation